2012
DOI: 10.4489/kjm.2012.40.3.152
|View full text |Cite
|
Sign up to set email alerts
|

Production of Lignocellulytic Enzymes from Spent Mushroom Compost of Pleurotus eryngii

Abstract: were extracted from spent mushroom compost (SMC) of Pleurotus eryngii. Different extraction buffers and conditions were tested for optimal recovery of the enzymes. The optimum extraction was shaking incubation (200 rpm) for 2 h at 4 o C. α-Amylase was extracted with the productivity range from 1.20 to 1.6 Unit/SMC g. Cellulase was recovered with the productivity range from 2.10 to 2.80 U/gf. β-glucosidase and β-xylosidase productivities showed lowest recovery producing 0.1 U/g and 0.02 U/g, respectively. The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…3 ). A previous study showed that the SMC of P. eryngii can digest FP [ 15 ] and the results indicated that the enzymes extracted from the SMC of Pleurotus have industrial value. Thus, the results of this study showing that the SMC extracts of P. cornucopiae and P. eryngii can digest FP suggest that SMC can be used in production of bio-energy by degradation of biomass.…”
Section: Resultsmentioning
confidence: 99%
“…3 ). A previous study showed that the SMC of P. eryngii can digest FP [ 15 ] and the results indicated that the enzymes extracted from the SMC of Pleurotus have industrial value. Thus, the results of this study showing that the SMC extracts of P. cornucopiae and P. eryngii can digest FP suggest that SMC can be used in production of bio-energy by degradation of biomass.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was in accordance with growth profiles of fungal mycelia. Basidiomycetes, such as the oyster mushroom, king oyster mushroom, winter mushroom, and shiitake, can enzymatically degrade cultivation substrates containing lignin, hemicellulose, and cellulose into low molecular weight sugars, which are then absorbed by fungal hyphae to support growth and maturation in a process called nutritive absorption (Lim et al, 2012, 2013; Chen et al, 2016). In the late stage of mycelial maturation, the slowing of metabolism causes a decrease in the levels of extracellular enzymes, so the abundance of degradation products is correspondingly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The first studies were published in the early 2000s, when different solvent systems, including water, sodium citrate buffer, and sodium phosphate buffer, were evaluated to extract hydrolases and oxidoreductases from SMS of P. sajor-caju SMS [ 170 ] and P. ostreatus [ 171 ], the latter also included SMS of other species. In other studies, different buffers and conditions were evaluated for extraction of α-amylase, endoglucanase, laccase, and endoxylanase from SMS of P. eryngii, P. ostreatus , and P. cornucopiae ; the best recoveries were achieved using sodium citrate buffer [ 172 , 173 ]. Sadiq et al [ 174 ] used a sodium tartrate buffer for extracting manganese peroxidase (MnP), laccase, and lignin peroxidase (LiP) from P. ostreatus SMS and used the extract for bioremediation of contaminated soil.…”
Section: Spent Mushroom Substrate As Source Of Enzymes and Bioactive ...mentioning
confidence: 99%